Empirical methods for evaluating educational interventions - Phye, Gary D.; Robinson, Daniel H.; Levin, Joel R. (Educational psychology., 2005)
Invaluable for all educators and teachers needing to write acceptable grant proposals or to obtain governmental funding for their programs.